(untitled) (Forum for Linguistic Studies, 2024)
The radicalism movement, which is largely synonymous with the threat of violence today, is not only carried out by men, but also by women who began to participate in radical actions. The aim of this research is to analyze and reveal the communication patterns of female ulama in preaching against radicalism through the taklim assembly in Garut, West Java. This research uses a constructivist paradigm with qualitative methods through a case study approach. The selection of informants was carried out using a purposive sampling technique with data collection techniques carried out through observation, in-depth interviews, and documentation. The results of the research show that interpersonal communication is used by female ulama to package issues and messages through the taklim assembly, which prioritizes an attitude of openness and empathy to unravel the dangers of radicalism in religion. Interpersonal communication is carried out through message packaging by raising issues very close to women’s daily lives. This communication between female ulama in fighting radicalism in Garut, West Java is carried out through three patterns, namely, one-way communication, two-way communication, and multi-way communication (Effendy, 2011). One-way communication is carried out when giving lectures, two-way communication is carried out through discussion processes, and multi-way communication is through the efforts of women’s organizational networks and advocacy for controlling and preventing radicalism and religious extremism in Garut district. Meanwhile, communication barriers occur due to the closed attitude of some congregants, whether caused by takiyah (hiding identity), or culture with the aim of being polite towards scholars or teachers.